Arahan Garis Sempadan Muka Bangunan (GSMB) di Jalan Metro Tanjung Bunga, Kota Makassar - Aspar Nurdin; Arifuddin Akil; Slamet Trisutomo (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2020)
All this time, there are no detailed guidelines regarding the determination of the demarcation lines of building faces and the factors that need to be considered in determining them in Makassar City. This study aims to determine the factors that influence and how much influence it has in determining the boundary distance of the building face and to recommend directions needed for future implementation. This research was conducted from August 2019 to February 2020 (6 months). This research case study is around Jalan Metro Tanjung Bunga, by taking samples of residential and commercial areas. The data was collected by using field survey methods, questionnaires, interviews, and literature study. Data analysis was performed using the Delphi method to determine the factors, the Analytical Hierarchy Process (AHP) method to determine the level of influence of the factors, and the descriptive method to formulate the direction of the building front boundaries. The results of this study show that there are 17 factors that affect the demarcation lines of the building faces in the area, including fire disaster mitigation, provision of parking spaces, disaster evacuation areas, accessibility, provision of green open spaces and water infiltration. As for the direction in implementing the rules for building front boundaries in future case studies, it is necessary to consider the provision of disaster evacuation areas, especially in residential areas, and the provision of parking spaces, especially in commercial areas.